2021
DOI: 10.2174/1874350102114010033
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dominant Personality Traits on Team Roles

Abstract: Background: The Gulf region is notorious for importing Asian laborers for blue-collar work due to the cheap costs associated with it. With many languages and cultural barriers present, understanding the needs of these workers and their preferred methods of communication has proven to be a challenge. Their ways are often misinterpreted, both collectively and individually. From years of observation, these mishaps are primarily due to the lack of understanding and resources available to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Fourthly, e-learning assists in compensating for scarcities of academic staff, including instructors, facilitators, lab technicians, etc. Also, when English is a second language and ethnicity is considered, flexibility in learning channels may prove to be useful (Diab-Bahman, 2021a, b). Lastly, e-learning provides opportunities for interaction between learners through discussion forums, also by removing the fear barrier that hampers students' participation (Coldwell et al , 2008).…”
Section: Litreature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourthly, e-learning assists in compensating for scarcities of academic staff, including instructors, facilitators, lab technicians, etc. Also, when English is a second language and ethnicity is considered, flexibility in learning channels may prove to be useful (Diab-Bahman, 2021a, b). Lastly, e-learning provides opportunities for interaction between learners through discussion forums, also by removing the fear barrier that hampers students' participation (Coldwell et al , 2008).…”
Section: Litreature Reviewmentioning
confidence: 99%
“…However, the migration process was smooth for certain universities, while some reacted with crisis-response migration measures because of the pandemic (Hodges et al , 2020). Also, it was found that some universities were more prepared than others as some had been using VLEs as part of the learning process (Diab-Bahman, 2021a, b). Universities changing their conventional classroom delivery methods to e-learning forums were accompanied with few difficulties, one being that the change has caused necessary adjustment in the attitudes of universities, instructors and students on the importance of web-based learning (Ribeiro, 2020).…”
Section: Litreature Reviewmentioning
confidence: 99%